Case of Large Acrochordon on Inguinals - Idris, Irma Suryani (Jurnal Biologi Tropis, 2025)
Acrochordon or known as skin tag is a benign growth on the skin that is usually small and soft. However, in some rare cases, the size of acrochordon can enlarge significantly and is called large acrochordon. One case of giant acrochordon was reported in a 23-year-old woman at the dermatovenereology polyclinic of a hospital in Makassar. The diagnosis was made based on clinical features, histopathological examination. The results of the examination of this case from the anamnesis results obtained complaints of a lump that was initially small 6 years ago and then left to grow in number and enlarge. The results of the physical examination found 1 large soft mass with a stalk. The patient was treated with excision biopsy of the lesion and clinical improvement. Supporting examinations include histopathological biopsy examinations. This patient was treated with oral and topical antibiotics and analgesics after an excision biopsy and control after 7 days post-excision. Control day 7 excision wound is not perfectly dry and closed this is caused by damp and closed, the groin/inguinal area is often covered by clothing and sweats easily, creating a humid environment that is not ideal for wound healing. Control day 14, the wound dries and the overall aff hecting in this case 3 stitches, the pain is decreasing.